Two types of flexibility: in coping and cognitive, and their relationship with stress among firefighters - Agata Borzyszkowska; Małgorzata Anna Basińska (Medycyna Pracy, 2020)
Background Flexibility in coping with stress and cognitive flexibility are new constructs both in Polish and European psychological sciences. A person displaying flexibility in coping has a wide repertoire of remedial strategies, which he or she is able to change if the situation so requires, and which reflect on the strategies used, while a person displaying cognitive flexibility is ready to look for new ways to cope. The profession of a firefighter involves exposure to various stressors, and occupational stress can affect not only mental health, but also the quality of work performed. That is why flexibility in coping with stress and cognitive flexibility seem so important. The aim of the study was to perform empirical verification of the relationship between flexibility in coping and cognitive flexibility, as well as to determine their relationship with the stress perceived by the respondents.